1989
DOI: 10.1099/0022-1317-70-7-1837
|View full text |Cite
|
Sign up to set email alerts
|

Fate of African Cassava Mosaic Virus Coat Protein Deletion Mutants after Agroinoculation

Abstract: SUMMARYWe have investigated the behaviour of coat protein deletion mutants of the geminivirus African cassava mosaic virus (ACMV) when introduced into Nicotiana benthamiana by agroinoculation. In dividing callus tissue, replicating mutant DNA A, in the absence of DNA B, remained subgenomic in size. However, systemic infection of plants was associated with the rapid reversion of the deletion mutants to native component size, as happened when the mutants were introduced into the host by more conventional mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 26 publications
3
55
0
Order By: Relevance
“…2, lane 1 and results not shown). These results are similar to those found with two isolates of T G M V (Elmer et al, 1988;Frischmuth et al, 1993), ACMV (Klinkenberg et al, 1989), AbMV (Evans & Jeske, 1993) and Indian cassava mosaic virus (Frischmuth et al, 1993) and illustrates that as with these other bipartite geminiviruses, the PYMV D N A A component encodes all of the viral proteins necessary for viral D N A replication. Following agroinoculation of tomato and potato leaf discs with a mixture of pP2A and pP2B extracts of both were found to contain virus-specific, replicative supercoiled and genomic ssDNA of both PYMV DNA (Fig.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…2, lane 1 and results not shown). These results are similar to those found with two isolates of T G M V (Elmer et al, 1988;Frischmuth et al, 1993), ACMV (Klinkenberg et al, 1989), AbMV (Evans & Jeske, 1993) and Indian cassava mosaic virus (Frischmuth et al, 1993) and illustrates that as with these other bipartite geminiviruses, the PYMV D N A A component encodes all of the viral proteins necessary for viral D N A replication. Following agroinoculation of tomato and potato leaf discs with a mixture of pP2A and pP2B extracts of both were found to contain virus-specific, replicative supercoiled and genomic ssDNA of both PYMV DNA (Fig.…”
supporting
confidence: 77%
“…The ability of cloned dimeric PYMV DNAs to replicate in agroinoculated leaf discs derived from the same plants used in the whole plant agroinoculation experiments above was assayed as described previously (Elmer et al, 1988;Klinkenberg et al, 1989) in accordance with established procedures (Horsch & Klee, 1986). Axenically grown potato plants (Adams et al, 1985) were used as a source of sterile leaf tissue in preference to greenhouse-grown plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The deleted region in the progeny DNA A was replaced by cloning vector DNA sequestered from pUC DNA surrounding the DNA A fragment in the inoculated construct. Size reversion of ACMV DNA A has been shown previously for systemic infections resulting with coat protein deletion mutants (Etessami et al, 1989;Klinkenberg et al, 1989). Klinkenberg et al (1989) showed that the size reversion observed for ACMV DNA A with the coat protein deletion mutants was produced following systemic spread, whereas in dividing callus ceils the deleted DNA A was replicated.…”
Section: Agroinoculation Of Dna a Deletion Mutantsmentioning
confidence: 97%
“…Binary vector clones were introduced into Agrobacterium tumefaciens strain GV3850 (Zambryski et al, 1983) and used to agroinoculate Nicotiana benthamiana and A. conyzoides plants as described by Saunders et al (2004). N. benthamiana leaf disks were prepared and maintained as described by Klinkenberg et al (1989) and DNA was extracted from plant tissues and analysed by Southern blot hybridization as described by Saunders et al (2004). Equal amounts of DNA were loaded in each lane.…”
Section: Methodsmentioning
confidence: 99%